Fuzzy control on vehicle active suspension system - Muhamad Nazmi, Ahmad Nazari (2010)
The active suspension system is a possible way to improve suspension performance although the passive system can effectively handle some control of suspension system. The main propose of this project is to assess performance of active suspension system in comparison and passive suspension system by implementing Fuzzy and Proportional-Integral-Derivative. The quarter car system is designed and constructed based on the four wheel independent suspension. Mathematic model that used in simulation is based on the dynamic diagram of quarter car system. Passive suspension is a system that not equipped with any controller but there are two controllers that used in active suspension system. The two controllers that applied to simulate the action of active system are Fuzzy Logic controller and Proportional-Integral-Derivative controller. First controller that used in active system is PID controller. This controller design deals with the selection of proportional gain, derivative gain and integral gain parameters (K_p,〖 K〗_(d )and〖 K〗_i). The parameter of this control is adjusted by tuning the PID controller using the heuristic method. Fuzzy Logic controller is applied to the block diagram that controlled by PID controller to improve the active suspension system. From the result of simulations, the Fuzzy-PID scheme can reduce vibration than PID scheme. In conclusion, the active suspension with PID controller combined with FLC is more effective and stable rather than passive suspension system.